FACTORS INFLUENCE THE STABILITY OF ISLAMIC AND CONVENTIONAL BANKS IN GCC COUNTRIES - Nour, Ahmed Ali; Ali Alkhawla, Prof. Dr. Mohammed Abdullah; Mahyoub Al, Asst. Prof. Dr. Maged Mustafa; Al-Hodiany, Zakarya Mohsen Muthanna (IJRDO - Journal of Business Management, 2017)
This study examines the factors that affect banks’ stability in GCC Countries and investigates the stability of Islamic and Conventional banks for two periods 2006 to 2010 and 2011 to 2015. It covers 18 banks. There are several independent variables such as Liquidity, Cost efficiency, Income diversity, Total asset, GDP growth rate, and CPI while Z-score is used as dependent variable. Regression analysis was used to test the relationship between dependent and independent variables. Findings from the study show that there is a relationship between all independent variables and z-score and most importantly For the period of 2006 to 2010, the study concluded that all factors (Liquidity, Cost efficiency, Total asset, GDP growth rate, and CPI) have a positive relationship with z-score, but income diversity have negative relationship with the z- score and the period of 2010 to 2015, all factors (Liquidity, Cost efficiency, Total asset, and GDP growth rate) have a positive relationship with z-score, but income diversity and CPI have negative relationship with the z- score. The paper also found that Conventional banks are more stable in 2006 to 2010 and 2011 to 2015.